Green Human Resources Management on Turnover Intentions Mediated by Work Environment Employees - Andi Nur Insan; Asnawar Asnawar; Muhammad Nur; Masmarulan Masmarulan (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: This research has the aim of knowing and analyzing the role of green human resources, including green recruitment and training, and the work environment that influences employee intention to leave. Employees at Sultan Hasanuddin International Airport Makassar.Methodology: In this study, 105 samples were used and samples were taken from employees at Sultan Hasanuddin International Airport, Makassar. PLS was the data analysis tool used.Finding: The results of this study are (1) There is a direct effect of recruitment on the employee's intention to leave; (2) green training has a direct influence on intention to leave; (3) there is a direct significant relationship between the work environment and the intention to leave; (4) work environment indirect relationship is capable of mediating green recruitment process with a significant intention to leave; and (5) an indirect relationship where the work environment significantly mediates green training with employees' desire to leave during this time.Conclusion: The results of this study state that recruitment and training have a positive and significant effect on employee intention to leave, both directly and indirectly on the work environment.